(untitled) (KONFERENSIYA, 2025)
The article examines the lexical, syntactic, and semantic characteristics of medical technology English and explores effective translation strategies for rendering these structures into Uzbek. Special attention is given to the use of passive constructions, nominalization, and complex sentence patterns, which are highly frequent in scientific and technical medical texts. Through analytical examples extracted from professional medical discourse, the study identifies key linguistic challenges and proposes practical solutions for improving translation accuracy, clarity, and scientific objectivity. The findings contribute to enhancing the quality of medical translation and ensuring reliable knowledge transfer in healthcare communication